Lipids of Rhodotorula mucilaginosa IIPL32 with biodiesel potential: Oil yield, fatty acid profile, fuel properties. (3rd February 2017) - Khot, Mahesh; Ghosh, Debashish
Abstract : This study analyzes the single cell oil (SCO), fatty acid profile, and biodiesel fuel properties of the yeast Rhodotorula mucilaginosa IIPL32 grown on the pentose fraction of acid pre‐treated sugarcane bagasse as a carbon source. The yeast biomass from nitrogen limiting culture conditions (15.3 g L −1 ) was able to give the SCO yield of 0.17 g g −1 of xylose consumed. Acid digestion, cryo‐pulverization, direct in situ transesterification, and microwave assisted techniques were evaluated in comparison to the Soxhlet extraction for the total intracellular yeast lipid recovery. The significant differences were observed among the SCO yield of different methods and the in situ transesterification stood out most for effective yeast lipid recovery generating 97.23 mg lipid as FAME per gram dry biomass. The method was fast and consumed lesser solvent with greater FAME yield while accessing most cellular fatty acids present. The yeast lipids showed the major presence of monounsaturated fatty esters (35–55%; 18:1, 16:1) suitable for better ignition quality, oxidative stability, and cold‐flow properties of the biodiesel. Analyzed fuel properties (density, kinematic viscosity, cetane number) of the yeast oil were in good agreement with international biodiesel standards. The sugarcane bagasse‐derived xylose and the consolidated comparative assessment of lab scale SCO recovery methods highlight the necessity for careful substrate choice and validation of analytical method in yeast oil research. The use of less toxic co‐solvents together with solvent recovery and recycling would help improve process economics for sustainable production of biodiesel from the hemicellulosic fraction of cheap renewable sources.